2009
DOI: 10.1158/0008-5472.can-08-4700
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular β-Tubulin/Chaperonin Containing TCP1-β Complex Serves as a Novel Chemotherapeutic Target against Drug-Resistant Tumors

Abstract: In the present study, treatment of HEK-293 cells with the synthetic small molecule N-iodoacetyl-tryptophan

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 47 publications
2
52
1
Order By: Relevance
“…This is consistent with the recently published structure of CCT in complex with tubulin combined with crosslinking/MS analysis that suggests a direct interaction between the C-terminal domains of α-or β-tubulin and CCT2 [32]. This is also consistent with studies suggesting that the tubulin-CCT interaction is initiated by the C-terminal domain of tubulin [33,34]. A proteomic study on tubulin-binding proteins in plant cells identified CCT7 (TCP-1 η subunit) [35].…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with the recently published structure of CCT in complex with tubulin combined with crosslinking/MS analysis that suggests a direct interaction between the C-terminal domains of α-or β-tubulin and CCT2 [32]. This is also consistent with studies suggesting that the tubulin-CCT interaction is initiated by the C-terminal domain of tubulin [33,34]. A proteomic study on tubulin-binding proteins in plant cells identified CCT7 (TCP-1 η subunit) [35].…”
Section: Discussionsupporting
confidence: 91%
“…Both alpha-and beta-tubulin were identified in the L1 proteome, and various tubulin proteins have been shown to play a role in phagocytosis (31,41) and in regulation of apoptosis (42). A protein spot that matched lethal giant larvae homologue was found, and one possible function for this protein is the induction of salivary gland cell autophagic cell death.…”
Section: Discussionmentioning
confidence: 99%
“…Reduction of the CCT or CCT subunit could result in growth arrest, with significant alterations in cell morphology and motility [14]. Moreover, the CCT proteins promote the development of several tumor types, including breast cancer [4], colorectal cancer [7,24,27,28], uterine sarcoma [21], lung carcinoma [8,24], ovarian cancer [22], and multitudinous tumor cells [1,25]. Recent studies have suggested that CCT8 might be upregulated in colon, breast and hepatocellular carcinoma specimens [17,35,36].…”
Section: Introductionmentioning
confidence: 99%